Intervensi Strategis Untuk Mengoptimalkan Manajemen Diri Lansia Dengan Hipertensi (Systematic Review) - Silvia Elki Putri; Etty Rekawati (Jurnal Penelitian Kesehatan SUARA FORIKES, 2020)
Culture in Indonesia influences all aspects of society, including health such as beliefs related to health management, health behavior and health care. One of the aggregates of concern regarding health in Indonesia is the elderly. The elderly are a vulnerable group who are at risk of experiencing health problems. Elderly with hypertension requires good management in health care. The objective of this review was to exploring interventions strategy to optimize the self-management of the elderly with hypertension. The design employed was a systematic review. The data was obtained from Wiley Online Library, Science Direct, Proquest, Research Gate, Springer Link, Google Scholar, and national journals from 2009-2019. The articles collected in this systematic review use the keywords "hypertension" AND "elderly", "elderly self management with hypertension", "elderly compliance with hypertension in caring for themselves", and "self management guidance" as the keywords with text in Indonesian and English. The tittle and journal were esplores and chosen based on inclusion criteria and additional articles selected by screening with flow diagram PRISMA in the list of references in citations from this literature. The result of this review showed that interventions to optimize self-management of the elderly with hypertension were found to be 8 interventions, namely: (1) Introduction of hypertension, (2) Regular physical activity regulation, (3) Reduction of alcohol and cigarette consumption, (4) Management of stress and sleep rest, (5) Diet and weight management, (6) Blood pressure monitoring, (7) Social support, (8) Compliance with treatment regimens. Good self-management will affect the compliance of the elderly in optimizing their health. Keywords: hypertension; elderly; self management ABSTRAK Budaya di Indonesia mempengaruhi semua aspek masyarakat, termasuk kesehatan seperti kepercayaan yang terkait dengan manajemen kesehatan, perilaku kesehatan dan perawatan kesehatan. Salah satu agregat mendapatkan perhatian tentang kesehatan di Indonesia adalah lansia. Lansia adalah kelompok rentan yang berisiko mengalami masalah kesehatan. Lansia dengan hipertensi membutuhkan manajemen yang baik dalam perawatan kesehatan. Tujuan dari tinjauan sistematik ini adalah untuk mengeksplorasi intervensi strategis untuk mengoptimalkan manajemen diri lansia dengan hipertensi. Data diperoleh dari database Wiley Online Library, Science Direct, Proquest, Research Gate, Springer Link, Google Cendekia, dan jurnal nasional mulai dari 2009-2019. Artikel yang dikumpulkan dalam tinjauan sistematis ini menggunakan kata kunci “hypertension" AND "elderly", “elderly self management with hypertension”, “kepatuhan lansia dengan hipertensi dalam merawat diri”, dan "bimbingan manajemen diri" dengan teks dalam bahasa Indonesia dan Inggris. Judul dan jurnal dieksplorasi dan dipilih berdasarkan kriteria inklusi dan artikel tambahan dipilih dengan melakukan screening menggunakan diagram alur PRISMA dalam kutipan dari literatur ini. Hasil tinjauan ini menunjukkan bahwa terdapat 8 intervensi untuk mengoptimalkan manajemen diri lansia dengan hipertensi yaitu: (1) Pengenalan penyakit hipertensi, (2) Pengaturan aktivitas fisik yang teratur, (3) Pengurangan konsumsi alkohol dan rokok, (4) Manajemen stres dan istirahat tidur, (5) Pengaturan diet dan berat badan, (6) Memonitoring tekanan darah, (7) Dukungan sosial, (8) Kepatuhan dengan rejimen pengobatan. Manajemen diri yang baik akan mempengaruhi kepatuhan lansia dalam mengoptimalkan kesehatan lansia. Kata kunci: hipertensi; lansia; manajemen diri